ASSOCIATION OF FOOD INTAKE WITH METABOLIC SYNDROME AMONG FILIPINO ADULTS IN THE 8TH PHILIPPINE NATIONAL NUTRITION AND HEALTH SURVEY (NNHeS) - Lusica, Patricia Marie; Jimeno , Cecilia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The prevalence of metabolic syndrome among Filipino adults was found to be 12-15%. Diet has been one of the identified modifiable risk factors targeted to prevent disease or complications. The association of each macronutrient component with metabolic syndrome remains unclear. There is no Philippine data on macronutrient intake and metabolic syndrome. The primary objective of this study is to determine the association of food intake with metabolic syndrome among Filipino adults. METHODOLOGY This study utilized a cross-sectional analytic design. Data was obtained from the results of the 8th Philippine NNHeS done in 2013 from the Public Use Files of the Food and Nutrition Research Institute. Filipino adults from different regions of the Philippines who consented to participate in the interview, anthropometrics, blood collection for clinical data, and other measurements were included in this study. RESULTS There were 8,056 adults included in the 8th NNHeS. The prevalence of metabolic syndrome was 32%. Multivariate analysis showed that increased total protein intake (OR 1.391), and daily consumption of meat and poultry (OR 1.397), and condiments and spices (OR 1.329) were associated with increased risks for metabolic syndrome. Decreased vegetable intake was also associated with an increased risk for metabolic syndrome, as well as higher socioeconomic status, female sex, and old age. CONCLUSION Increased total protein intake, daily consumption of meat, poultry, condiments and spices, and decreased vegetable intake are associated with an increased risk for metabolic syndrome.